Developing a Neonatal Pulmonary Hypertension Core Outcome Set (NeoPH COS)—A Study Protocol - Cara Ellen Morgan; Kerry Woolfall; Natasharazia Aikman; Crhistopher Gale; Nimish Subhedar; the RePHyNe Consortium (Pulmonary Circulation)
ABSTRACT Pulmonary hypertension (PH) in newborn babies is a relatively rare, heterogeneous condition that has high associated mortality in the neonatal period and beyond. There are limited evidence‐based strategies to treat or prevent this condition. Over the last two decades, there has been an increase in the number of studies assessing new therapies and treatment strategies in babies with PH. However, comparison of different treatments between studies is limited by inconsistency in outcome reporting. To address this issue, we aim to develop a core outcome set (COS) for neonates and infants less than 3 months of age, corrected for prematurity, diagnosed with PH, through international consensus with key stakeholders including parents and/or guardians, healthcare professionals and researchers. The development of the COS will be divided into two stages: (1) identification of potential outcomes through a mixed methods systematic literature review and qualitative interviews with parents and/or guardians of babies with pulmonary hypertension; (2) determining core outcomes through an online Delphi survey and consensus meeting. An advisory group with global membership including parents and/or guardians, healthcare professionals, and researchers recruited internationally was formed to guide the COS. The methodology utilized to develop a neonatal PH COS aims to ensure applicability and adoption in international settings and relevance across disciplines. The COS will help to improve trial design and homogeneity of outcomes reported in neonatal trials of PH. This will translate into higher‐quality evidence for therapeutic strategies for PH in neonates.